Occurrence of hourglass dolphin (Lagenorhynchus cruciger) and habitat characteristics along the Patagonian Shelf and the Atlantic Ocean sector of the Southern Ocean - Dellabianca, N.; Scioscia, G.; Schiavini, A.; Raya Rey, A. (Polar Biology, 2012)
The hourglass dolphin, Lagenorhynchus cruciger, is one of the smallest cetaceans found in Antarctic waters. Although frequently observed, this is one of the least studied species of dolphin. In this study, we investigate the occurrence of hourglass dolphin in the South-West Atlantic and Southern Ocean from 42A degrees S to 63A degrees S and characterize the oceanographic and environmental features associated with their occurrence. Sighting data were collected during two scientific cruises in December 2009 and January and February 2011 and integrated into a geographical information system with environmental variables such as sea surface temperature, ocean colour, depth, distance to oceanographic fronts and distance from shore. We used a principal component analysis (PCA) to identify patterns in data and a non-hierarchic cluster analysis (K means) to classify observations into groups. A total of 19 sightings (96 individuals) were recorded. Group size ranged from one to twelve dolphins (mean 5.05). We could differentiate two groups in relation to the environmental conditions where animals were found, one group occurring in shallow coastal waters and the other occurring in deeper and colder waters further offshore. The present study contributes novel information on environmental measures associated with hourglass dolphin distribution in the South-West Atlantic and Southern Oceans. Additionally, it includes relatively high sighting clusters of this species in two highly productive and biodiverse areas (Burdwood Bank/Isla de los Estados and the South Shetland Islands). Published